Dialogic focalization in Ashwin Sanghi’s The Krishna Key - Al Ogaili, Thamer Amer Jubouri; Mani, Manimangai; Jujar Singh, Hardev Kaur; Awang, Mohammad Ewan (Center for Resource, Research and Publication Services, 2018)
This article focuses on the dialogic focalization in Ashwin Sanghi’s The Krishna Key (2012). The study will mainly focus on the narrative construction of the novel. The novel abounds with narrative elements, such as narrative point of view which plays an integral role in providing the reader with the whole impression of the plot. Accordingly, this study will shed light on one narrative component in the selected novel i.e., the dialogic focalization. In essence, the dialogic feature of the novel carries out the authorial implied voice in the plot. The author, Sanghi, has some ideological notions and expresses them in the text. This is the monologic characteristic of the dialogic structure of the novel. On the other hand, the text has some characters who exemplify the author’s ideological insights in the plot. This is the polyphonic, or dialogic, characteristic of the dialogic element in the novel. For this reason, my study will examine the dialogic voice in the novel to explore the authorial narrative focalization. The authorial focalization will be discussed in terms of the author’s implied presence in the text in order to draw the reader’s attention to its dialogic structure. Thus, Gérard Genette’s concept of the focalization factor and Mikhail Bakhtin’s concept of the dialogic novel will be applied to analyze the selected novel’s narrative structure.